Differences among religiously unaffiliated and Christians in the perceptions of the personality of Jesus - Rouse, Steven V. (2018)
Previous research has demonstrated that Christians living in Korea and Christians living in the US differ in their perceptions of Jesus, in a manner that is aligned with cultural values. The present study examined differences in the perception of Jesus within the US, examining agnostics, atheists, Catholics and nondenominational Christians, specifically assessing perceptions of his personality traits and moral foundations. Differences were observed between Christian groups and religiously unaffiliated groups, especially on the perceived levels of Agreeableness, Conscientiousness, and respect for Authority. However, among Christians, nondenominational Christians perceived higher levels of Conscientiousness, Openness, and respect for Authority than Catholics did. Finally, agnostics perceived higher levels of Agreeableness, Conscientiousness, and Compassion and lower levels of Neuroticism than atheists did.
Keywords: Agnosticism; Atheism; Christianity; Religious Beliefs